Glucoside-3-cyanidin (Cy3G) and its importance in cancer therapy - Piątek, Małgorzata; Polaniak, Renata; Kiciak, Agata; Staśkiewicz, Wiktoria; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
When analyzing the structure of cancer incidence in Poland, it is extremely important to take chemopreventive actions as early as possible, which are aimed at reducing the incidence of the most common cancers, focusing on the prevention and use of natural bioactive factors contained in food. Anthocyanins are a large group of ingredients contained in plants that do not have a nutritional function, but play a significant role in the regulation of metabolic processes in the human body, which has a multidirectional pro-health and preventive effect in relation to many diseases, especially cancer. High hopes in chemoprevention are associated with the biological activity of the most common representative of anthocyanins, i.e. cyanidin-3-glucoside (Cy3G). Most of the studies on Cy3G bioactivity come mainly from in vitro cell line tests and in vivo experimental studies on rodents. Studies of the biological activity of Cy3G most often include: the process of free radical absorption, anti-inflammatory, anticoagulant, insulinotropic, antimicrobial, chemotherapeutic and epigenetic effects. This publication summarizes the results of in vitro studies conducted on various cancer cell lines, which prove the antiproliferative, anti-inflammatory and chemopreventive activity of Cy3G.